Transcatheter aortic valve implantation not preceded by balloon valvuloplasty in a patient with increased risk of stroke – a case report - Zimoch, Wojciech; Kustrzycka-Kratochwil, Dorota; Telichowski, Artur; Falkiewicz, Zdzisław; Kubler, Piotr; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Until recently, balloon valvuloplasty (BAV) was considered as a necessary step during transcatheter aortic valve implantation (TAVI). It was proven that BAV increases the risk of stroke and conduction disturbances requiring permanent pacemaker implantation. Omitting aortic valvuloplasty can increase the safety of percutaneous treatment of severe aortic stenosis.